Age-Related Tortuosity of Carotid and Vertebral Arteries: Quantitative Evaluation With MR Angiography - Sun, Zhe; Jiang, Dengrong; Liu, Peiying; Muccio, Marco; Li, Chenyang; Cao, Yan; Wisniewski, Thomas M.; Lu, Hanzhang; Ge, Yulin (Frontiers in Neurology, 2022)
Background and Purpose: Vascular tortuosity (VT) of the internal carotid artery (ICA) and vertebral artery (VA) can impact blood flow and neuronal function. However, few studies involved quantitative investigation of VT based on magnetic resonance imaging (MRI). The main purpose of our study was to evaluate the age and gender effects on ICA and VA regarding the tortuosity and flow changes by applying automatic vessel segmentation, centerline tracking, and phase mapping on MR angiography. Methods: A total of 247 subjects (86 males and 161 females) without neurological diseases participated in this study. All subjects obtained T1-weighted MRI, 3D time-of-flight MR angiography, and 2D phase-contrast MRI scans. To generate quantitative tortuosity metrics from TOF images, vessel segmentation and centerline tracking were implemented based on Otsu thresholding and fast marching algorithms, respectively. Blood flow and velocity were measured using PC MRI. 144 subjects (≤60 years, 49 males/ 95 females) were categorized as the young group; 103 subjects (>60 years, 37 males/ 66 females) were categorized as the old group. Results: Independent t-test showed that older subjects had higher tortuosity metrics, whereas lower blood flow and velocity than young subjects (P < 0.0025, Bonferroni-corrected). Cerebral blood flow (CBF) calculated using the sum flux of four target arteries normalized by the brain mass also showed significantly lower values in older subjects (P <0.001). Age was observed to be positively correlated with VT metrics. Compared with males, females demonstrated higher geometric indices within VAs as well as faster age-related vascular profile changes. After adjusting age and gender as covariates, maximum blood velocity is negatively correlated with geometric measurements. No association was observed between blood flux and geometric measures. Conclusions: Vascular auto-segmentation, centerline tracking, and phase mapping provide promising quantitative assessments of tortuosity and its effects on blood flow. Neck arteries demonstrate quantifiable and significant age-related morphological and hemodynamic alterations. Moreover, females showed more distinct vascular changes with age. Our work is built upon a comprehensive quantitative investigation of a large cohort of populations covering adult lifespan using MRI, the results can serve as reference ranges of each decade in the general population.